Sustainable Electricity Production Using Avocado Waste - Rojas-Flores, Segundo (2023)
Agroindustry waste has exponentially increased in recent years, generating economic losses and environmental problems. In addition, new ways to generate sustainable alternative electrical energy are currently being sought to satisfy energy demand. This investigation proposes using avocado waste as fuel for electricity generation in single-chamber MFCs. The avocado waste initially operated with an ambient temperature (22.4 ± 0.01 °C), DO of 2.54 ± 0.01 mg/L, TDS of 1358 ± 1 mg/L and COD of 1487.25 ± 0.01 mg/L. This research managed to generate its maximum voltage (0.861 ± 0.241 V) and current (3.781 ± 0.667 mA) on the fourteenth day, operating at an optimal pH of 7.386 ± 0.147, all with 126.032 ± 8.888 mS/cm of electrical conductivity in the substrate. An internal resistance of 67.683 ± 2.456 Ω was found on day 14 with a PD of 365.16 ± 9.88 mW/cm2 for a CD of 5.744 A/cm2. Micrographs show the formation of porous biofilms on both the anodic and cathodic electrodes. This study gives preliminary results of using avocado waste as fuel, which can provide outstanding solutions to agro-industrial companies dedicated to selling this fruit.